2017
DOI: 10.1111/codi.13549
|View full text |Cite
|
Sign up to set email alerts
|

Does a more extensive mucosal excision prevent haemorrhoidal recurrence after stapled haemorrhoidopexy? Long‐term outcome of a randomized controlled trial

Abstract: The study failed to demonstrate any significant difference in the long-term recurrence rate of Stage III haemorrhoids using EEA or PPH. Nevertheless, use of the larger volume EEA provides better symptom resolution compared with PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Giuratrabocchetta et al reported that the DST stapler can resect a significantly larger area of mucosa than the PPH stapler due to the wider capacity of its shaft case 14 , and a similar result was found in the present study. Although recurrence prolapse is more likely to be due to remove inadequate volume of prolapse mucosa 23 , there is no difference in recurrence rate between DST and PPH stapler in a long-term randomized control trial 24 .…”
Section: Discussionmentioning
confidence: 93%
“…Giuratrabocchetta et al reported that the DST stapler can resect a significantly larger area of mucosa than the PPH stapler due to the wider capacity of its shaft case 14 , and a similar result was found in the present study. Although recurrence prolapse is more likely to be due to remove inadequate volume of prolapse mucosa 23 , there is no difference in recurrence rate between DST and PPH stapler in a long-term randomized control trial 24 .…”
Section: Discussionmentioning
confidence: 93%
“…It was planned that 64 patients would be enrolled in each group to allow for violations of the protocol and/or non-evaluable patients. The value of ▵ = 0.23 was based on the difference in the 6-month cure rate between the historical MLPPH cure rate (91 per cent) in the authors’ department and the SH cure rate (68 per cent) in articles published before 2018 15 .…”
Section: Methodsmentioning
confidence: 99%